2018
DOI: 10.1177/0954405418805601
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rotational speed on mechanical features of thermally drilled holes in dual-phase steel

Abstract: Thermal drilling is a novel chipless sheet metal drilling process that uses a rotating thermal drill tool to pierce and form a bushing shape hole. In this work, thermal drilling process is successfully employed to drill the DP 600 grade–type galvanized steel with a thickness of 2 mm. The influence of different spindle rotational speeds such as 1600, 2000 and 2400 r/min on the formation of bushing height, surface roughness, microhardness and microstructure of the thermal-drilled holes are investigated in detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Hynes & R. R. Kumar & Hynes, 2018a, 2018bRajesh, Hynes, Kumar, & A. J. Sujana, 2017) is performed before making a connection of sheet metals and the fabricated holes performance as a location of stress concentration. Therefore, augmented care is given to the failure possibilities in the drilled hole which is created by the action of creep and fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Hynes & R. R. Kumar & Hynes, 2018a, 2018bRajesh, Hynes, Kumar, & A. J. Sujana, 2017) is performed before making a connection of sheet metals and the fabricated holes performance as a location of stress concentration. Therefore, augmented care is given to the failure possibilities in the drilled hole which is created by the action of creep and fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed from the research that by increasing spindle speed, roughness was less, bushing height was high and axial force was less. R Kumar et al concluded that higher spindle speed is optimum for friction drilling [54].…”
Section: Somasundrammentioning
confidence: 99%
“…Kumar and Hynes [5] investigated the effect of rotational speed on mechanical characteristics during thermal drilling. The results revealed that better surface quality could be achieved at a higher rotational speed of 2400 rpm.…”
Section: Introductionmentioning
confidence: 99%